Plan de Reactivación Agroturística en el sitio Mendoza del Cantón Junín Provincia de Manabí - Rogel Morán, Mayra Elizabeth (2013)
This thesis is about an Agrotouristic Reactivation Plan in the Site of Mendoza, Canton of Junín, Province of Manabí, which is underlined due to the insufficient agrotouristic alternatives that exist in the area, despite the fact that they have some natural resources of tourist potential that can be well spent if training is given to the community. General purpose: Design a plan to revive tourism as of the advice to the community for the creation of agrotouristic farms for the use and exploitation of natural resources of the area. For this, we have considered five chapters: In the first chapter, we provide an introduction to the proposal, the problems are brought up, we establish the general and specific objectives as well as justification. The second chapter deals with the research design and the different means used to obtain the public and tourists' points of view. The third chapter outlines the proposed project and the analysis of economic, environmental and cultural impacts, the layout of the agrotouristic farm is shown. The fourth chapter cites the marketing plan based on strategies to attract tourists. The fifth and final chapter provides financial analysis under the following parameters; projections of revenue, cost analysis, cash flow, NPV and IRR financial evaluation analysis. It also presents the general conclusions that were reached with this proposal which meets with the general and specific purpose of the thesis.